4 -(-19) = 23
Step-by-step explanation:
-(- = +
I hope this help ^^
Hey there!
Guide #1
• 2 negatives = positive
• 2 positives = positive
• 1 negative & 1 positive = negative
• 1 positive & 1 negative = negative
Guide #2
• Negatives are BELOW 0
• Positives are ABOVE 0
Guide #3
• Positives are on the RIGHT side of 0 (and on the number line)
• Negatives are on the LEFT side of 0 (and on the number line)
Guide #4
• When dealing with negatives you go down
• When dealing with positives you go up
ANSWERING YOUR QUESTION
4 - (-19)
= 4 + 19
• You start with 19 (because it is the bigger number in this case) and go up 4 spaces to your right
= 23
Therefore, your answer should be: 23
Good luck on your assignment and enjoy your day!
~Amphitrite1040:)
Does the table represent a proportional or a nonproportional linear relationship?
x 1 2 3 4 5
y 5 7 9 11 13
The table represents a linear relationship.
Answer please?
Factor the GCF:
102−5
please help me out
Step-by-step explanation:
what do we need to do ? find the 0 solutions for x ?
if that is the case, let's just do all the multiplication first :
(3/2)² × (2/3)⁴x² = x
9/4 × 16/81 x² = x
4/9 x² = x
4/9 x² - x = 0
4x² - 9x = 0
x × (4x - 9) = 0
so, one solution is obviously x = 0.
the second solution is
4x - 9 = 0
4x = 9
x = 9/4
An artifact originally had 16 grams of carbon-14 present. The decay model A = 16 e -0.0001211 describes the amount of carbon-14 present after t years. Use the mode
to determine how many grams of carbon-14 will be present in 9088 years
The amount of carbon-14 present in 9088 years will be approximately
grams.
The mass of Carbon-14 left according to the decay model after 9088 years will be; 5.3229 grams
The decay model is given as;
A = 16 e^ (-0.0001211t)Therefore, after 9088 years; in which case; t = 9088.
The amount of Carbon-14 that will be present is;
A = 16e^ (-0.0001211 × 9088)A = 16e^(-1.1005)A = 5.3229gramsRead more:
https://brainly.com/question/24305651
Simplify.
(x2 - y2 - 3xy) + (7xy + 3x2)
Answer:
(x² - y² - 3xy) + (7xy + 3x²) = 4x² - y² + 4xy
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
Brackets Parenthesis Exponents Multiplication Division Addition Subtraction Left to RightAlgebra I
Terms/CoefficientsStep-by-step explanation:
Step 1: Define
Identify
(x² - y² - 3xy) + (7xy + 3x²)
Step 2: Simplify
[Order of Operations] Combine like terms (x²): (x² - y² - 3xy) + (7xy + 3x²) = 4x² - y² - 3xy + 7xy[Order of Operations] Combine like terms (xy): (x² - y² - 3xy) + (7xy + 3x²) = 4x² - y² + 4xyAnswer:
4x^2-y^2+4xy
Step-by-step explanation:
Just combine like terms and do not forget that your adding the set of parentheses together.
x^2+3x^2
-y^2
-3xy+7xy
what number is six more than 1/3 of 90? step by step I have a test tomorrow and I don't know any math
Answer:
36
Step-by-step explanation:
First, just multiply 90 by 1/3. 90 is equal to 90/1 as any number divided by 1 is still equal to itself.
[tex]\frac{90}{1}*\frac{1}{3}=\frac{90*1}{1*3}=\frac{90}{3}[/tex]
Now, 90/3 is just 90 ÷ 3.
[tex]90 \div 3 = 30[/tex]
Finally, just add 6 to it.
[tex]30+6=36[/tex]
Answer:
36
Step-by-step explanation:
1/3 of 90 is 30
6 more is 30+6=36
is y-4x=9 linear or not linear. if yes, write in standard form
Answer:
Yes it is linear. Standard Form: 4x - y = -9
Step-by-step explanation:
find the zeros of y=x^3-x^2-9x+9
with explanation
Answer:
So, we have the equation:
[tex]y=x^3-x^2-9x+9[/tex]
Usually, we have to do trial-by-error methods like using the Rational Root Theorem to factor cubic polynomials. However, while this may seem like a complicated cubic equation to factor, it has a simple trick to make it much easier!
We can actually factor this polynomial through Factoring by Grouping. With this method, we can factor a cubic polynomial. We split the equation into two parts, like this:
[tex]y=x^3-x^2-9x+9[/tex]
[tex]y=(x^3-x^2)+(-9x+9)[/tex]
Which can be simplified to:
[tex]y=(x^2)(x-1)+(-9)(x-1)[/tex]
We took out a factor of x^2 for the first term and a negative 9 for the second term. As we can see, we now have two terms that are the same:
(x - 1)
We can factor out the (x - 1) like this:
[tex]y=(x^2)(x-1)+(-9)(x-1)[/tex]
[tex]y=(x-1)(x^2-9)[/tex]
Now, this is not the most simplified form. See the x^2-9 term? We can use the Difference of Squares.
In general:
[tex]a^2-b^2=(a-b)(a+b)[/tex]
We have the expression:
[tex](x^2-9)=(x^2-3^2)[/tex]
[tex](x^2-3^2)=(x-3)(x+3)[/tex]
Therefore:
[tex]y=(x-1)(x^2-9)[/tex]
[tex]y=(x-1)(x-3)(x+3)[/tex]
Our fully factored form for y=x^3-x^2-9x+9 is:
[tex]y=(x-1)(x-3)(x+3)[/tex]
Carly is playing the Integer Game. She draws four cards: -3, -8, 9, 4. What is the value of her hand?
Answer:
-3+-8+9+4= 2
Hope this helps.
Answer:
The value is positive 2
Step-by-step explanation:
(-3)+(-8)=(-11)
9+4=13
(-11)+ 13=2
Y = 2X
- 6X + 3y = 6
What is the common ratio?
512, 256, 128, 64
Answer:
The constant factor between consecutive terms of a geometric sequence is called the common ratio. Example: To find the common ratio find the ratio between a term and the term preceding it. r=42=2. 2 is the common ratio.
How to calculate the area of an ellipse by using integration?
An ellipse has the general equation
(x/a)² + (y/b)² = 1
(actually, this is an ellipse whose semimajor and -minor axes are parallel to the x- and y-axes, but one can rotate any ellipse so that it has the same configuration, and the area remains constant)
Convert to a kind of rescaled polar coordinates, using
x = a r cos(t)
y = b r sin(t)
Then the interior of such an ellipse is the set
E = {(r, t) : 0 ≤ r ≤ 1 and 0 ≤ t ≤ 2π}
The area of E is then given by the integral
[tex]\displaystyle \iint_E dA[/tex]
Compute the Jacobian determinant for this change of coordinates. The Jacobian is
[tex]J = \begin{bmatrix}x_r & x_t \\ y_r & y_t\end{bmatrix} = \begin{bmatrix}a \cos(t) & -a r \sin(t) \\ b \sin(t) & b r \cos(t)\end{bmatrix}[/tex]
Then we have Jacobian determinant
|det(J)| = |a b r cos²(t) + a b r sin²(t)| = |a b r| = |a b| r
since r ≥ 0.
The area of E is then
[tex]\displaystyle \iint_E dA = \iint_E |ab| r \, dr \, dt[/tex]
[tex]\displaystyle \iint_E dA = \int_0^{2\pi} \int_0^1 |ab| r \, dr \, dt[/tex]
[tex]\displaystyle \iint_E dA = 2\pi |ab| \int_0^1 r \, dr[/tex]
[tex]\displaystyle \iint_E dA = \boxed{\pi |ab|}[/tex]
w(x)=3x-1; FInd w(-2)
Answer:
It is 23
Step-by-step
23 becaauae if you use x and -2 its bets 23
What is the factored form of 3x+24y?
3(x+8y)
3xy(x+8y)
3(3x+24y)
3xy(3x+24y)
Answer:
[tex]\boxed{\boxed{\sf 3(x+8y)}}[/tex]
Step-by-step explanation:
[tex]\sf 3x+24y[/tex]
Factor out the GCF( Write GFC first, then, in parentheses divide each term by the GCF).
GCF: → 3
[tex]\leadsto\sf \textsf{\:}3\left(\cfrac{3x}{3}\:+\cfrac{24y}{3}\right)[/tex]
Simplify each term in parentheses:
[tex]\leadsto\sf 3(x+8y)[/tex]
_______________________________________
Answer:
A. 3(x+8y)
Step-by-step explanation:
Just did it
simplify: -5/3(-6-9x)
Answer:
jsbnsjzskjusjjw.3334883!"!$+%-$+$9
When 1,500 flowers are divided equally among 40 baskets, there are 20 flowers
in each basket
in half of the baskets
left over
Answer:
in half of the baskets
Step-by-step explanation:
half of 40 baskets is 20 baskets
subtract X from 3X minus one
What is the measure of angles A, B and C in the given triangles?
Answer:
A = 103°; B = 77°; C = 46°
Step-by-step explanation:
A + 45° + 32° = 180°
A + 77° = 180°
A = 180° - 77°
A = 103°
A + B = 180°
103° + B = 180°
B = 180° - 103°
B = 77°
B + C + 57° = 180°
77° + 57° + C = 180°
134° + C = 180°
C = 180° - 134°
C = 46°
I hope I've helped you.
A group of people were asked whether they prefer soup or salad for lunch.
The table shows the probabilities of the results
Let A represent having soup and B represent having salad for lunch.
Which statement is true?
A. Having soup and salad for lunch are independent events because P(A]B) = P(A) and P(BA) = P(B)
B. Having soup and salad for lunch are independent events because P(A]B) + P(A) and P(BA) + P(B)
C. Having soup and salad are not independent events because P(A]B) + P(A) and P(BA) + P(B)
D. Having soup and salad for lunch are not independent events because P(A]B) = P(A) and P(BA) = P(B)
Answer:
Having soup and salad for lunch are independent events because P(A/B)=P(A) and P(B/A) = P(B)
Step-by-step explanation:
If you help ill mark as brilliant.
I need help with surface area
Answer:
904.8 m²
Step-by-step explanation:
needed formulas:
surface of a circle: πr²
circumference of a circle: 2πr
The top and bottom are circles with radius 9, and surface π9² = 81π m²
The side is a rectangle of 2·π·9·7 long, so that is 126π m²
Brings the total to 81π + 81π + 126π = 288π ≈ 904.8 m²
can someone please help me with this
Answer:
use your protractor if you had one you can find the measurement of the angle ABD .
30 pts answer correct plzzzz
Answer:
b
Step-by-step explanation:
b is correct
Answer:
Option 1
Step-by-step explanation:
∠EGB ≅ ∠EHD {Corresponding angles
∵ ∠AGF ≅∠EHD {transitive equality property}
Write a word translation for 7 >x.
Answer:
mashup math on "yt"
Step-by-step explanation:
go there you'll get you answer and more he explained it better then i could have
What is the slope of the line through (-1,4) and (1,-2)? A.-3 B.3 C.-1/3 D.1/3
Answer:
Slope = - 3
Step-by-step explanation:
Formula : -
Slope = ( y2 - y1 ) / ( x2 - x1 )
( x1, y1 ) = ( - 1, 4 )
Here,
x1 = - 1
y1 = 4
( x2, y2 ) = ( 1, - 2 )
Here,
x2 = 1
y2 = - 2
Slope = ( - 2 - 4 ) / ( 1 - ( - 1 ) )
= - 6 / ( 1 + 1
= - 6 / 2
Slope = - 3
Therefore,
The slope of the line through ( - 1, 4 ) and ( 1, - 2 )
is - 3.
4. Which information can you read from an equation that is written in slope-intercept form?
slope
x-intercept
origin
distance between the c-intercept and the y-intercept
Tell what number you would add to each side of the inequality.
Please answer ASAP
Answer: 6
Step-by-step explanation: Gets x by itself.
One number is one more than another. Their sum is nine. Find both numbers.
Answer:
4 and 5
Step-by-step explanation:
Let's make an equation to solve. Let's call "one number" x. Another number is 1 more than x, so now we have x + 1. x plus x + 1 is equal to 9... and this gives us our equation:
x + (x + 1) = 9
We can now simplify by adding like terms together:
2x + 1 = 9
Now, let's take away 1 from both sides:
2x = 8
We can finally divide both sides by 2 to isolate x:
x = 4
One of our numbers is 4. Our other number is one more than 4, and 4 + 1 = 5. So our numbers are 4 and 5.
Hopefully this was helpful! If you need more help, let me know.
A(0, 1), B(2,7)
find the slope of the lime that passes through each pair of points. show work and solve.
Answer:
The slope is 3
Step-by-step explanation:
[tex]m = \frac{7 - 1}{2 - 0} \\ m = \frac{6}{2} \\ m = 3[/tex]
Simplify: 3√50+√24-2√72
Answer: 72
Step-by-step explanation:
i took the k12 test